KEBIJAKAN PENDIDIKAN DASAR DAN TANTANGAN IMPLEMENTASINYA DI SDIT PADANG ISLAMIC SCHOOL - Roza Naulia Rosdianti; Nia Ikhtanova; Anita Ulpa; Firsty Sofila; Adellar Prasetya; Rahmatul Husna; Dewi Fitriana (STKIP Subang, 2025)
Educational policies at the elementary level play a strategic role in shaping the quality, equity, and effectiveness of basic education. However, the implementation of these policies in schools often faces various challenges. This study aims to analyze elementary education policies and identify the main challenges in their implementation at the school level through a literature review. The research employed a literature study method by reviewing national and international journal articles, policy documents, and academic books related to basic education policy and school management. Data were collected through systematic searches of academic databases and analyzed using thematic analysis. The results reveal that major challenges in implementing basic education policies include limited school resources, disparities in infrastructure, teachers’ readiness, leadership capacity of school principals, bureaucratic complexity, and gaps between policy design and school contexts. Despite well-formulated policies, implementation effectiveness largely depends on coordination among stakeholders, school management capacity, and contextual adaptability. This study concludes that strengthening institutional capacity, improving policy coherence, and enhancing support systems for schools are essential to address implementation challenges and ensure the successful realization of basic education policy goals.